protocols.io 2019
DOI: 10.17504/protocols.io.yfxftpn
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of general and specific cognitive precursors of early mathematical performance v1

Abstract: The main goal of this study was to analyse, using structural equation modeling, the contribution of predictors of both domain-general (working memory, processing speed and receptive vocabulary) and domain-specific (estimation and magnitude comparison) processes to informal mathematical performance (numbering, comparison, calculation and understanding of concepts) in preschoolers. A total of 158 preschool students (ages ranging from 52 to 64 months) participated in the investigation. Students were assessed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
2
5
0
6
Order By: Relevance
“…It is plausible to argue that number estimation may be related to magnitude representation and the ability to recognize and employ diverse ways to problem resolution. The study's predictive value backs with previous research that found a link between number estimate competence and mathematics proficiency (ARAGÓN et al, 2019;SASANGUIE;VAN DEN BUSSCHE;REYNVOET, 2012), specifically when it comes to conceptual arithmetic knowledge . Thus, it is clear that the ability to correctly estimate the location of numbers on a straight line necessitates knowledge of the number system and additive composition, which refers to the notion that every natural number is made up of the addition of smaller numbers.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It is plausible to argue that number estimation may be related to magnitude representation and the ability to recognize and employ diverse ways to problem resolution. The study's predictive value backs with previous research that found a link between number estimate competence and mathematics proficiency (ARAGÓN et al, 2019;SASANGUIE;VAN DEN BUSSCHE;REYNVOET, 2012), specifically when it comes to conceptual arithmetic knowledge . Thus, it is clear that the ability to correctly estimate the location of numbers on a straight line necessitates knowledge of the number system and additive composition, which refers to the notion that every natural number is made up of the addition of smaller numbers.…”
Section: Discussionsupporting
confidence: 76%
“…Some studies emphasize the value of working memory for mathematical achievement in relation to general domain skills, indicating that it is a precursor skill to initial mathematical learning (ARAGÓN et al, 2019;GEARY, 2011;VERCELLONI;SCHADEE, 2007;LANFRANCHI, 2012;XENIDOU-DERVOU et al, 2018) and demonstrating significant improvements in children's performance since kindergarten and remaining with positive effects throughout elementary school. Working memory is a memory system that allows people to temporarily regulate, store, and process relevant information while performing cognitive tasks (BADDELEY, 2011;RAGHUBAR;BARNES;HECHT, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientific literature focused on addressing the development of early mathematical cognition sustains the meaning of training different skills as a cognitive basis for learning math (Geary et al, 2013;Aragón et al, 2014Aragón et al, , 2020Soto-Calvo et al, 2015;Malone et al, 2019;Pace et al, 2019). These skills also provide the development of a solid background in early numeracy, which is considered critically important for later mathematical achievement (Ramani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%